2017
DOI: 10.1007/s40262-017-0513-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Lysergic Acid Diethylamide in Healthy Subjects

Abstract: Background and ObjectiveLysergic acid diethylamide (LSD) is used recreationally and in clinical research. The aim of the present study was to characterize the pharmacokinetics and exposure–response relationship of oral LSD.MethodsWe analyzed pharmacokinetic data from two published placebo-controlled, double-blind, cross-over studies using oral administration of LSD 100 and 200 µg in 24 and 16 subjects, respectively. The pharmacokinetics of the 100-µg dose is shown for the first time and data for the 200-µg dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
103
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 41 publications
23
103
5
Order By: Relevance
“…In the present study, we found no evidence of acute pharmacological tolerance within 12 h of acute LSD administration at a dose of 100 μg as documented in detail elsewhere (Dolder et al, 2017). Similarly, no acute tolerance was observed after single-dose administration of 200 μg LSD in humans within 24 h (Dolder et al, 2015b, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, we found no evidence of acute pharmacological tolerance within 12 h of acute LSD administration at a dose of 100 μg as documented in detail elsewhere (Dolder et al, 2017). Similarly, no acute tolerance was observed after single-dose administration of 200 μg LSD in humans within 24 h (Dolder et al, 2015b, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Visual Analog Scales (VASs) were repeatedly used to assess subjective effects over time . The VASs included separate measures for “any drug effect,” “good drug effect,” “bad drug effect”, and “the boundaries between myself and my surroundings seemed to blur” (ego dissolution) and were presented as 100 mm horizontal lines (0–100%) marked from “not at all” on the left to “extremely” on the right.…”
Section: Methodsmentioning
confidence: 99%
“…The predicted concentrations were then used as an input to the PD model by treating the PK parameters as fixed and using the classic PK/PD link model module in WinNonlin. The model used a first‐order equilibrium rate constant ( k eo ) that related the observed PD effects of LSD to the estimated LSD concentrations at the effect site and accounted for the lag between the plasma and effect site concentration curves . A sigmoid maximum effect ( E max ) model (EC 50 , E max , γ) was selected for all PD effects: E = ( E max × C p h )/( C p h + EC 50 h ), in which E is the observed effect, C p is the plasma LSD concentration, E max is the maximal effect and h is the Hill slope using WinNonlin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent pilot studies point to the potential of psychedelic‐assisted therapy to treat conditions including tobacco and alcohol addiction, obsessive‐compulsive disorder , end of life anxiety/depression , major depression , and TRD – (see Carhart‐Harris & Goodwin, 2017 for a review ). Intriguingly, the treatment effect in these trials appears to last for several months – much longer than the pharmacological presence of the actual compounds .…”
Section: Introductionmentioning
confidence: 99%